On some traditional symbols in Soviet holiday journalism - Ткаченко, Юлія Валеріївна; Трифонов, Роман Анатолійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is devoted to finding out the features of traditional symbols ‘light’, ‘sun’, ‘fire’ and related to them in Ukrainian Soviet journalistic texts written and published for different holidays. The three basic ways of symbol use according to O. Potebnya (comparison, opposition, causal relation) are analyzed, the differences of their functioning in folk-poetic and ideologized world language pictures are pointed out. The characteristics of symbol usage such as selectivity, tendency to monosemanticity, aiming to create emotions are found out.